ANALISIS PEMBIAYAAN GRIYA TAKE OVER DAN DAMPAKNYA DENGAN AKAD MURABAHAH (Studi Pada BSI Cabang Bone) - Sari, Mirna; Haslindah; Shadriyah (MBISKU: Jurnal Manajemen Bisnis dan Keuangan, 2025)
This study aims to determine how the takeover mechanism (debt transfer) in an effort to overcome problematic credit and to determine the impact of Customers taking over (debt transfer) at BSI KC Bone. Based on the objectives of the study, this study uses a qualitative research method using observation, documentation and interview techniques as data collection techniques. Based on the results of the study, the takeover mechanism (debt transfer) is that customers submit an application, complete the completeness of the documents, the bank verifies the data, there is approval for takeover financing (debt transfer), then binding, finally disbursement. The impact for BSI is to increase the BSI bank margin, while for customers it is to get additional funds, can extend the installment period, a solution when finances are unhealthy, can transact according to sharia.